Portable bathtub: technology for bed bath in bedridden patients - Dirce Stein Backes; Carine Alves Gomes; Simone Barbosa Pereira; Noelucy Ferreira Teles; Marli Terezinha Stein Backes
ABSTRACT Objective: determine the benefits of the Portable Bathtub as technology for bed bath in bedridden patients. Method: qualitative research of exploratory-descriptive character, whose data were collected by means of 30 interviews with patients, family members and professionals directly involved in bed bath, carried out with Portable Bathtub, in bedridden patients of a medical clinic, from July to December 2015. Results: from the data encoded by thematic content analysis resulted two categories: Portable Bathtub: from morphine to the patient's rekindled eyes; From mechanized practice to unique, transforming care. Conclusion: we concluded that the Portable Bathtub constitutes enhancing technology, as it enables clinical improvement of the patient's general condition and transcends traditional mechanized practices by the reach of advanced nursing care practices.